Optimization of in vitro model for analysis of tumor cell migration dynamics - Kravchenko, A.O.; Kosach, V.R.; Shkarina, K.A.; Zaiets, I.V.; Tykhonkova, I.O.; Khoruzhenko, A.I. (Вiopolymers and Cell, 2018)
Migration ability is an important feature of tumor cells. There are several approaches to analyze the dynamics of cancer cell migration in vitro. One of the most perspective and closer to the in vivo conditions is the model of initiation of the cell migration from 3D multicellular spheroids onto growth surface. Aim. Optimization of the model for adequate quantitative characteristics of the tumor cell locomotion during several days. Methods. 2D and 3D MCF-7 cell culture, immunofluorescence analysis, and image analysis using computer software Fiji. Results. Unification of spheroid size allowed avoiding a significant data deviation. The obtained spheroids spread completely for 3 days. The highest migration ratio was observed at the 2nd day. The proliferation level at each of 3-day experiment was the same and did not exceed 3%. The validity of the model was tested after migration inhibition by rapamycin (mTOR signaling inhibitor). Additionally, this model was successfully applied to immunofluorescence analysis, namely investigation of p85S6K1 subcellular localization in moving MCF-7 cells. Conclusions. Double filtration of multicellular spheroids allowed unification of their size, which promotes an adequate interpretation of the migration assay. This model enabled the study of tumor cells migration dynamics and can be further used for the development of anticancer drug. Міграційна здатність є важливою ознакою пухлинних клітин. Існує кілька підходів до аналізу динаміки міграції ракових клітин in vitro. Однією з найбільш перспективних і близьких до умов in vivo є модель ініціювання міграції клітин з тривимірного багатоклітинного сфероїда на ростову поверхню. Мета. Оптимізація моделі для адекватної кількісної оцінки міграції пухлинних клітин. Методи. 2- та 3-вимірна культура клітин лінії MCF-7, імунофлюоресцентний аналіз, аналіз зображень з використанням комп'ютерної програми Фіджі. Результати. Уніфікація розміру сфероїдів дозволила уникнути значного розкиду даних. Отримані сфероїди повністю розпластувались протягом 3 днів. Найвищий показник міграції спостерігався на 2-гу добу розпластування сфероїда. Рівень проліферації клітин за кожну добу 3-денного експерименту був майже однаковим і не перевищував 3%. Валідність моделі була протестована після пригнічення міграційної активності клітин під впливом рапаміцину (інгібітор сигналізації mTOR). Крім того, запропонована модель була успішно застосована для дослідження субклітинної локалізації p85S6K1 в мігруючих клітинах лінії MCF-7 за допомогою імунофлюоресцентного аналізу. Висновки. Подвійне фільтрування багатоклітинних сфероїдів дозволяє уніфікувати їх розміри, що в подальшому сприяє адекватній оцінці міграційного потенціалу клітин. Запропонована модель дозволяє вивчати динаміку міграційних процесів пухлинних клітин і може бути використана для тестування протипухлинних препаратів in vitro. Миграционная способность является важной особенностью опухолевых клеток. Существует несколько подходов для анализа динамики миграции раковых клеток in vitro. Одной из наиболее перспективных и приближенных к условиям in vivo является модель инициации миграции клеток из трехмерных многоклеточных сфероидов на поверхность роста. Цель. Оптимизация модели для адекватных количественных характеристик локомоции опухолевых клеток в течение нескольких дней. Методы. 2D и 3D MCF-7 клеточная культура, иммунофлуоресцентный анализ и анализ изображений с использованием компьютерного программного обеспечения Фиджи. Результаты. Унификация размеров сфероидов позволила избежать значительного отклонения данных. Полученные сфероиды распространились полностью за 3 дня. Самый высокий коэффициент миграции наблюдался на 2-й день. Уровень пролиферации в каждом из 3-дневных экспериментов был одинаковым и не превышал 3%. Достоверность модели была проверена после ингибирования миграции рапамицином (ингибитор передачи сигналов mTOR). Кроме того, эта модель была успешно применена для иммунофлуоресцентного анализа, а именно для исследования субклеточной локализации p85S6K1 в движущихся клетках MCF-7. Выводы. Двойная фильтрация многоклеточных сфероидов позволила унифицировать их размер, что способствует адекватной интерпретации анализа миграции. Эта модель позволила изучить динамику миграции опухолевых клеток и может быть в дальнейшем использована для разработки противоопухолевого препарата.